2011
DOI: 10.3762/bjnano.2.26
|View full text |Cite
|
Sign up to set email alerts
|

Detection of interaction between biomineralising proteins and calcium carbonate microcrystals

Abstract: SummaryThe natural composite nacre is characterised by astonishing mechanical properties, although the main constituent is a brittle mineral shaped as tablets interdispersed by organic layers. To mimic the natural formation process which takes place at ambient conditions an understanding of the mechanism responsible for a defined microstructure of nacre is necessary. Since proteins are assumed to be involved in this mechanism, it is advantageous to identify distinct proteins interacting with minerals from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Distinct diffraction peaks at 26°, 27°, 33°, 36°, 38°, 41°, 43°, 46°, 48° and 50° confirmed the aragonite type of biocement crystals 20 . A sharp peak at 2θ = 22º in diffraction pattern indicates the presence of silicates in the biocement 21,22 . Different bacterial species induce different polymorphs of CaCO 3 crystals.…”
Section: Production Of Biocement From Tap Water Using Bacillus Cereusmentioning
confidence: 99%
“…Distinct diffraction peaks at 26°, 27°, 33°, 36°, 38°, 41°, 43°, 46°, 48° and 50° confirmed the aragonite type of biocement crystals 20 . A sharp peak at 2θ = 22º in diffraction pattern indicates the presence of silicates in the biocement 21,22 . Different bacterial species induce different polymorphs of CaCO 3 crystals.…”
Section: Production Of Biocement From Tap Water Using Bacillus Cereusmentioning
confidence: 99%
“…Together with other proteins of the organic matrix, one function proposed for Perlucin is the nucleation of aragonite crystals [13] , [32] by binding to aragonite instead of calcite, [33] . In calcium carbonate precipitation experiments, native Perlucin clearly leads to faster precipitation of CaCO 3 [13] .…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, it has been reported that aragonite has a surface area almost ten times higher than that of calcite, justifying a higher adsorption efficiency for mass unit of CaCO3. 27 The experimental data indicate that the amount of dye entrapped within calcium carbonate increases increasing its concentration solution. On the other side, the percentage of dye removed from the solution during the crystallization process decreases with its concentration.…”
mentioning
confidence: 98%